2019
DOI: 10.1108/md-06-2018-0669
|View full text |Cite
|
Sign up to set email alerts
|

Challenges with big data analytics in service supply chains in the UAE

Abstract: Purpose The purpose of this paper is to study the challenges associated with big data analytics (BDA) in service supply chains in the United Arab Emirates (UAE). Design/methodology/approach A comprehensive questionnaire has been developed based on semi-structured interviews with different administrators and IT experts. In the second phase, data (n=164) are collected from procurement, operations, administration and customer service staff in the UAE. In the third phase, responses are examined using principal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 108 publications
0
35
0
Order By: Relevance
“…Perceived benefits, technology complexity, data quality, IT infrastructure/capabilities, financial readiness, and top management support Khan [68] Propose a framework to address challenges in employing BDA for service supply chains.…”
Section: Diffusion Of Innovation Theory (Doi) and Technologyorganization-environment (Toe) Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived benefits, technology complexity, data quality, IT infrastructure/capabilities, financial readiness, and top management support Khan [68] Propose a framework to address challenges in employing BDA for service supply chains.…”
Section: Diffusion Of Innovation Theory (Doi) and Technologyorganization-environment (Toe) Frameworkmentioning
confidence: 99%
“…Employing diffusion of innovation (DOI) theory and the technology-organizationenvironment (TOE) framework, Lai et al [67] found that perceived benefits and top management support can significantly influence the adoption intention of BDA, and environmental factors and supply chain connectivity can significantly moderate the direct relationships between driving factors and the adoption intention. Khan [68] employed multiple theories/views (i.e., stakeholder theory, resource-based view, transaction cost economics, and systems theory) to explore challenges in adopting BDA and demonstrated that technical, cultural, ethical, operational, tactical, procedural, functional, and organizational factors have a significant impact on BDA adoption and the highest and lowest impacts come from ethical and technical factors.…”
Section: Raut Et Al [72]mentioning
confidence: 99%
“…Thus, the paper adds to the body of knowledge of big data in supply chain context with empirical founded research which is deemed in shortage (Kache and Seuring, 2017). In a service context, challenges of the value creation of big data include technical, cultural, ethical, operational, tactical, procedural, functional and organizational challenges (Khan, 2019). By establishing strategic alignment capabilities, a company can improve its utilization of big data and thus mitigate or overcome these challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the diverse challenges of the value creation of big data is thus needed. Service supply chains are considered to develop efficient ways to use all the data that comes from different channels (Cohen, 2018; Khan, 2019; Opresnik and Taisch, 2015; Zhong et al , 2016). Big data affects several extant practices why it is paramount to uncover how these practices are related to each other for achieving a higher level of alignment and thus a higher performance-related value created from big data.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Extant literature has studied ‘Data Science Strategy’ in the contexts of dynamic market places, organizational and dynamic capabilities (Knabke & Olbrich, 2018 ), innovations (Mikalef et al 2018 , 2019a ), and new product development processes (Johnson et al 2017 ). Studies have been conducted in the context of but not limited to healthcare (Chen and Banerjee 2020 ; Kamble et al 2019 ; Kemppainen et al 2019 ; Li et al 2021 ; Newlands et al 2020 ; Ramnath et al 2020 ; Yang et al 2015 ; Wang and Hajli 2017 ), B2B (Hallikainen et al 2020 ), construction (Ahmed et al 2018 ; Ram et al 2019 ; Sang et al 2020 ), supply chain management (Ali et al 2020 ; Arunachalam et al 2018 ; Brinch et al 2018 ; Dubey et al 2019a ; Khan 2019 ; Lai et al 2018 ; Lamba and Singh 2018 ; Mandal 2019 ; Singh and Singh 2019 ; Wang et al 2018c ), manufacturing (Popovič et al 2018 ; Verma 2017 ), consumer goods (Rialti et al 2018 ); e-commerce (Behl et al 2019 ; Wamba et al 2017 ), telecommunications (Saldžiūnas and Skyrius 2017 ; Walker and Brown 2019 ), banking and financial services (Lee et al 2017 ; Lautenbach et al 2017 ; Gregory 2011 ), automotive (Dremel et al 2017 ), and airlines (Holland et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%